Gender bias in fetal malformations: A cross-sectional study in Asian populations - Zhang, Meixiang; Su, Yingchun; Sun, Ying-pu (Frontiers in Endocrinology, 2023)
Objectives: The aim of this study was to detect any gender bias in fetal malformation cases. Design: This study was a cross-sectional, quantitative survey. Subjects: Overall, 1,661 Asian fetal malformation cases involving induced abortions in the obstetrics department of the first Affiliated Hospital of Zhengzhou University from 2012 to 2021 were included. Main Outcome Measures: Measurements of ultrasound detectable structural malformations were classified into 13 subtypes. Karyotyping, single nucleotide polymorphism (SNP) array, or sequencing diagnosis of these fetus was also included in the outcome measures. Results: The sex ratio (male/female) of all malformation types was 1.446. Cardiopulmonary had the highest proportion of all malformation types with 28%. Diaphragmatic hernia, omphalocele, gastroschisis, nuchal translucency (NT) and multy-malformations had significantly higher proportions of males (p<0.05). Digestive system malformations had a significantly higher proportion of females (p<0.05). Maternal age was associated with genetic factors (r=0.953, p<0.001) and inversely associated with brain malformations (r=-0.570, p=0.002). More males were found with trisomy 21, trisomy 18, and monogenetic diseases, while duplications, deletions, and uniparental disomy (UPD) had similar sex ratios between males and females, but not statistically significant. Conclusions: Sex differences are common with fetal malformations, with higher proportions of males. Genetic testing has been proposed to account for these differences.